Analisis Faktor yang Mempengaruhi Kinerja Jaringan Komputer dalam Lingkungan Multi-User - Fitrian, Harry Pribadi; Difa, Damia Hasna; Vina Aulia Melianti; Fajar Muhammad Ramdhani (Universitas Methodist Indonesia, 2025)
This study addresses the degradation of computer network performance in multi-user environments due to high traffic loads, limited bandwidth, and suboptimal configurations, leading to reduced throughput, increased delay, jitter, and packet loss. The objective is to identify key influencing factors and effective optimization techniques through a Systematic Literature Review (SLR) of empirical studies from 2020-2025. The methodology involved searching databases like Google Scholar and Garuda using keywords such as